Impact of COVID Pandemic on the Mental Well-Being of Orthopaedic Patients – A Single Centre Study - Riaz Ahmed, Junaid Khan, Rahman Rasool Akhtar, Talia Urooj (Journal of Rawalpindi Medical College, 2021)
Objectives: To assess the frequency of psychiatric diseases in orthopaedic patients during the COVID-19 pandemic. Material and methods: This study was conducted from 20th April 2020 to 20th September 2020 at the Department of Orthopaedics, Benazir Bhutto Hospital, Rawalpindi, Pakistan. Patients aged 18 years and above and belonging to either gender with Orthopaedic injuries were included. Gender, age, injury mechanism, associated trauma, site of fracture, use of tobacco and mental health disorder was recorded. Data was analyzed using SPSS version 23. Results: The study included 210 patients with Orthopaedic injuries. Mean age of patients in the study was 40.45±12.54 years. Falls were the most common mechanism of injury (50.4%) followed by motorcycle accidents (22.8%) and motor vehicle accidents (16.7%). 70.47% patients with Orthopaedic injuries were diagnosed with a mental health problem. There were notably higher rates of depression (33.1%) and anxiety (24.3%). Conclusion: There was a high frequency of psychiatric illnesses in Orthopaedic patients during the COVID-19 pandemic. Keywords: COVID-19, mental well-being, orthopaedic injuries, psychiatric illness.